Molecular docking and physicochemical studies of 1,3-benzodioxole tagged Dacarbazine derivatives as an anticancer agent - Sonaxi Kharb; Sangeeta Yadav; Anshul Singh; Anjana Sarkar; Ravi Tomar (Artificial Cells, Nanomedicine, and Biotechnology, 2023)
AbstractCancer, the biggest cause of death globally, remains a tough illness despite enormous advances in therapy. In the present study, 1,3-benzodioxole-tagged dacarbazine derivates were investigated as microtubule inhibitors in order to control cancer as microtubules are involved in cell proliferation. The tubulin protein was analyzed and its structure was validated by various protein validation tools. The binding potential of 1,3-benzodioxole-based dacarbazine-tagged derivatives with tubulin was checked using molecular docking software HEX 8.0 CUDA and AutoDock Vina. Swiss ADME online Web server and pkCSM are used for studying pharmacokinetic and pharmacological studies of compounds. The docking analysis ADME studies displayed that Compounds 1 and 2 bind effectively with the tubulin protein and showed potential properties to use as a potent anticancer drug.